Community resilience 2.0: Toward a comprehensive conception of community-level resilience. Issue 5 (20th October 2017) - Vaneeckhaute, Lieselotte E.; Vanwing, Tom; Jacquet, Wolfgang; Abelshausen, Bieke; Meurs, Pieter
Abstract: Resilience theory provides an applicable framework for studying how systems cope, adapt or transform in face of exogenous disruptions. We attempt to develop a comprehensive conception of community-level resilience; we propose a combination (i.e. social-ecological resilience, community resilience) of characteristics of systems-centered (e.g. structure, embeddedness in larger spatial and temporal scales) and components-centered conceptions of resilience. Well-developed communal resources and agency are considered components leading to community resiliency. Unfortunately, current literature on community resilience does not elaborate on social structures that condition agency of social agents. We believe Archers' morphogenetic approach and her stratified view of agency offers a seminal starting point. Furthermore, we suggest that forces (e.g. social, economic, natural) operating at larger levels impact communal resources; a community's social memory influences their agency. Finally, we make recommendations on how community development processes can strengthen community resilience in practice and how to conduct empirical research toward community resilience 2.0.